Moderating Role of Religiosity on Islamic Financial Inclusion & Literacy on the Decision to Save at Islamic Banks - Septi Istina; Mufti Alam Adha; Riduwan Riduwan (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
The presence of Islamic banks benefits society by meeting financial needs and following Islamic principles. Based on a case study of vocational school students majoring in Islamic Banking in Yogyakarta, this research focuses on the influence of religiosity as a moderating factor on Islamic financial literacy and the decision to save at an Islamic bank. This research aims to analyze the impact of Islamic financial literacy and inclusion on the decision to save at Islamic banks among vocational school students majoring in Islamic Banking in Yogyakarta, with religiosity as the moderating variable. This quantitative research uses questionnaires to collect data, with a sample as large as the number of respondents. The data are analyzed using the Test for Moderated Regression Analysis and SPSS 2. The results aim to reveal how these factors influence the decision to save at Islamic banks and their impact on Islamic financial education. The research results show that Islamic financial literacy and inclusion partially influence the savings decisions of vocational school students majoring in Islamic Banking at Islamic banks. The moderated regression analysis test shows that religiosity can moderate Islamic financial literacy and inclusion in the decisions of vocational school students majoring in Islamic Banking at Islamic banks.Keywords: Islamic Financial Literacy, Islamic Financial Inclusion, Decision to Save, Religiosity.